Production and characterization of lentivirus vector-based SARS-CoV-2 pseudoviruses with dual reporters: Evaluation of anti-SARS-CoV-2 viral effect of Korean Red Ginseng - Jeonghui Moon; Younghun Jung; Seokoh Moon; Jaehyeon Hwang; Soomin Kim; Mi Soo Kim; Jeong Hyeon Yoon; Kyeongwon Kim; Youngseo Park; Jae Youl Cho; Dae-Hyuk Kweon (Journal of Ginseng Research, 2023)
Background: Pseudotyped virus systems that incorporate viral proteins have been widely employed for the rapid determination of the effectiveness and neutralizing activity of drug and vaccine candidates in biosafety level 2 facilities. We report an efficient method for producing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pseudovirus with dual luciferase and fluorescent protein reporters. Moreover, using the established method, we also aimed to investigate whether Korean Red Ginseng (KRG), a valuable Korean herbal medicine, can attenuate infectivity of the pseudotyped virus. Methods: A pseudovirus of SARS-CoV-2 (SARS-2pv) was constructed and efficiently produced using lentivirus vector systems available in the public domain by the introduction of critical mutations in the cytoplasmic tail of the spike protein. KRG extract was dose-dependently treated to Calu-3 cells during SARS2-pv treatment to evaluate the protective activity against SARS-CoV-2. Results: The use of Calu-3 cells or the expression of angiotensin-converting enzyme 2 (ACE2) in HEK293T cells enabled SARS-2pv infection of host cells. Coexpression of transmembrane protease serine subtype 2 (TMPRSS2), which is the activator of spike protein, with ACE2 dramatically elevated luciferase activity, confirming the importance of the TMPRSS2-mediated pathway during SARS-CoV-2 entry. Our pseudovirus assay also revealed that KRG elicited resistance to SARS-CoV-2 infection in lung cells, suggesting its beneficial health effect. Conclusion: The method demonstrated the production of SARS-2pv for the analysis of vaccine or drug candidates. When KRG was assessed by the method, it protected host cells from coronavirus infection. Further studies will be followed for demonstrating this potential benefit.